1995
DOI: 10.1080/03014469500004152
|View full text |Cite
|
Sign up to set email alerts
|

Genetic correlates of menarcheal age: a multivariate twin study

Abstract: Multivariate genetic models were fitted to data from 44 pairs of MZ and 42 pairs of DZ twin girls on weight, height, and skeletal maturation at the age of menarche, in order to obtain information on genetic relationships of those measures with the age of menarche. The relationships of all three physical measures with this age were largely genetically controlled, but a genetic system controlling skeletal maturity was identified as the only genetic determinant of menarcheal age, independent of those systems of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 16 publications
1
28
0
1
Order By: Relevance
“…He found instead that height velocity was a far stronger predictor than weight, suggesting that the timing of menarche is determined by the rate of maturation not body size. Twin studies also show that the genetic control of sexual maturation is independent of the corresponding genetic system determining body size (Loesch et al 1995).…”
Section: Menarcheal Factorsmentioning
confidence: 99%
“…He found instead that height velocity was a far stronger predictor than weight, suggesting that the timing of menarche is determined by the rate of maturation not body size. Twin studies also show that the genetic control of sexual maturation is independent of the corresponding genetic system determining body size (Loesch et al 1995).…”
Section: Menarcheal Factorsmentioning
confidence: 99%
“…Age at menarche is known to be influenced by genetic factors (Loesch et al, 1995;Meyer et al, 1991) as well as by variables such as the degree of urbanization (Pasquet et al, 1999), the socioeconomic status (Henneberg and Louw, 1995), the number of children in the family, and the order of birth (Apraiz, 1999). Other factors such as nutrition (Simodon et al, 1997), seasonality (Boldsen, 1992), physical activity (Malina, 1983), and altitude (Gonzales et al, 1996) also have shown a significant effect on age at menarche.…”
mentioning
confidence: 99%
“…Other important factors are associated with age at menarche: genetic predisposition (Baxter-Jones et al, 1994;Loesch et al, 1995;Malina et al, 1994;Stager and Hatler, 1988), low body mass or low body fat content (Frisch, 1990), dietary behavior (Bale et al, 1996;Hamilton et al, 1988), family size (Malina et al, 1979;1997;Veronesi and Gueresi, 1994), and socioeconomic status (Bielicki et al, 1986;Łaska-Mierzejewska, 1995;Veronesi and Gueresi, 1994). Menarche is significantly later in rural Polish populations (Łaska-Mierzejewska, 1995).…”
Section: Discussionmentioning
confidence: 97%
“…Menarcheal ages of mothers and daughters and sisters points to familial dependence. Studies of twins, mothers and daughters, and sisters indicate a significant genetic effect in the timing of menarche (BaxterJones et al, 1994;Bergman and Orczykowska-Ś wia tkowska, 1988;Loesch et al, 1995;Malina et al, 1994;Stager and Hatler, 1988;Treloar and Martin, 1990). Other sources of variation in timing of this maturational event may include inappropriate diet, low nutritional status, and low body fat (Bale et al, 1996;Frisch, 1990;Kissinger and Sanchez, 1987;Łaska-Mierzejewska, 1993), which are associated with later menarche.…”
mentioning
confidence: 96%